The Invisible Barrier: Literacy and Its Relationship with Oral Health (Blackwell Synergy, 2005)
Although oral health in the United States has improved significantly over time,preventable and treatable oral diseases remain common, especially among the poor and underserved. Limited literacy skills among adults are hypothesized to be one of many barriers to better oral health outcomes.